Hubungan Konsumsi Makanan Cepat Saji Dengan Kejadian Obesitas Pada Remaja Sekolah Menengah Atas - Nurhasanah Syaharuddin; Ayu Sri Wahyuni (Barongko: Jurnal Ilmu Kesehatan, 2026)
Background: Obesity in adolescents is a growing health problem and carries a risk of developing degenerative diseases in adulthood. One factor suspected to play a role is unhealthy eating habits, particularly the consumption of fast food, which is high in calories, fat, sugar, and salt. Objective: This study aimed to determine the relationship between fast food consumption and obesity among high school (SMA) adolescents. Methods: This study used a quantitative design with a cross-sectional approach. The sample consisted of 120 high school students selected using a stratified random sampling technique. Data on fast food consumption were collected through a consumption frequency questionnaire, while obesity status was determined based on Body Mass Index (BMI/Age). Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Results: The results showed that adolescents with high fast food consumption were more likely to be obese than those with low consumption (p = 0.002). Conclusion: There is a significant relationship between fast food consumption and obesity among high school adolescents.